Effect Of Commercial Biofertilizer Product Of Seaweed (Euchema Cottonii) Towards The Growth Of Pakcoy Mustard (Brassica Rapa L) and Dumbo Catfish (Clarias Gariepinus) in Aquaponic System - Oktaviana Elsa Dewi; Sapto Andriyono; Mochammad Amin Alamsjah (Journal of Marine and Coastal Science, 2020)
Aquaponics is a technology that combines the cultivation of vegetable production and fish farming. The aquaponics technology also to fertilization to give nutrients to the plant to support of survival. In facts, fertilization done to plants is located on land. Fertilizing the plants that live in the waters are still very rare, because the waters as a growing medium that is considered to always provide sufficient nutrients for plant growth. In this research, using biofertilizer Euchema cottonii of seaweed. The advantages of biofertilizer seaweed is to have the content of macro and micro nutrients are complete. It also contains substances hyper Grow (PGR) plant (auxin, cytokinin, gibberellin, abisat acid and ethylene).In this research to determine the effect of biofertilizer products of seaweed (E. cottonii) commercial on the growth of dumbo catfish (C. gariepinus) and pakcoy mustard (B. rapa L) on aquaponics system. The design of experiments in this research using a completely randomized design (CRD) with 5 treatments and 4 replications. The treatment used is fertilizer "AB mix®" 1% (A), without fertilizer (B) and the provision of products biofertilizer seaweed (E. cottonii) commercial 0,16% (C), 0,18% (D) and 0,20% (E). The main parameters measured were heavy growth of biomass, plant height pakcoy mustard (B. rapa L), growth SGR, length and survival rate of fish of dumbo catfish (C. gariepinus).The results showed that the dose of different commercial product biofertilizer seaweed (E. cottonii) gives a significantly different effect on the height growth of pakcoy mustard (B. rapa L) and the survival rate of dumbo catfish (C. gariepinus). The optimal dosage of commercial seaweed (E. cottonii) biofertilizer product in increasing the growth of pakcoy mustard (B. rapa L.) and African catfish (C. gariepinus) in the aquaponic system, namely treatment E at a dose of 0.20%.